Separable Topological Space of Hereditary - Yadav, Raj Narayan; Regmi, Bed Prasad; Pathak, Surendra Raj (NUTA Journal, 2020)
A property of a topological space is termed hereditary ifand only if every subspace of a space with the property also has the property. The purpose of this article is to prove that the topological property of separable space is hereditary. In this paper we determine some topological properties which are hereditary and investigate necessary and sufficient condition functions for sub-spaces to possess properties of sub-spaces which are not in general hereditary.